Responses of zebrafish to chronic environmental stressors: anxiety-like behavior and its persistence - Li, Xiao-hong; Fu, Cheng; Tan, Xue-ting; Fu, Shi-jian (Frontiers in Marine Science, 2025)
IntroductionFish in natural ecosystems face long-term environmental stressors, with anxiety being a critical stress response. This study investigates how chronic stressors—predators, social isolation, and caffeine—affect anxiety-like behavior and cortisol levels in zebrafish (Danio rerio), and examines the persistence of these effects post-stressor removal.MethodsZebrafish were exposed to three stressors for 14 days. Anxiety-like behavior and cortisol levels were measured for up to 28 days following the removal of the stressors.ResultsChronic predator stress significantly increased anxiety-like behavior and cortisol levels, persisting for at least seven days post-removal. Social isolation reduced anxiety-like behavior and cortisol levels, with effects lasting no less than one day after re-socialization. Caffeine induced temporary anxiolytic effects, reversing one day post-withdrawal and persisting for at least seven days, while cortisol levels remained elevated.DiscussionZebrafish exhibit stressor-specific behavioral and physiological changes with varying persistence. These findings enhance understanding of fish responses to environmental stressors, offering insights into their survival strategies and ecosystem health.